2020
DOI: 10.1016/j.nicl.2020.102399
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter effectiveness trial of QEEG-informed neurofeedback in ADHD: Replication and treatment prediction

Abstract: Highlights QEEG-informed neurofeedback resulted in remission rates of 55%. In the total sample, non-remitters had higher hyperactivity scores at baseline. In women, non-remitters had longer P300 latencies. In boys, a low individual alpha peak frequency (iAPF) was associated with remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 68 publications
2
34
0
Order By: Relevance
“…Second, Kropotov et al 43 used a relative beta protocol, and similarly showed high ES for pre-post effects (1.07). Third, Krepel et al 38 used individual QEEG to assign participants to one of the standard protocols thus replicating Arns et al 37 in a multicentric study with a large sample. When the participants of these two open-label studies were pooled together, the acute pre-post ES was large (1.97) and a remission rate of 57% was observed.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Second, Kropotov et al 43 used a relative beta protocol, and similarly showed high ES for pre-post effects (1.07). Third, Krepel et al 38 used individual QEEG to assign participants to one of the standard protocols thus replicating Arns et al 37 in a multicentric study with a large sample. When the participants of these two open-label studies were pooled together, the acute pre-post ES was large (1.97) and a remission rate of 57% was observed.…”
Section: Resultsmentioning
confidence: 98%
“…In Monastra et al 20 and iCAN 22 studies ADHD children were pre-selected based on elevated theta-beta ratios and subsequently treated with TBR NF. Similarly, in the two open-label studies by Arns et al and Krepel et al 37 , 38 the baseline QEEG informed the decision to assign the ADHD patients to one of the three standard protocols (SCP, SMR or TBR). As shown in Figure 1 , the pre-post ESs were larger in the NF personalized interventions (1.40 for the TBR iCAN, 1.46 for the TBR and 1.97 for the QEEG informed) than when participants were randomized to non-personalized standard protocols (1.02 for SCP, 0.84 for SCP & TBR, 0.55 for TBR and 0.44 for SMR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has some limitations related to its nature (being a consecutive study, being gender unbalanced, and having no sham group). Although an unbalanced boys/girls ratio is common in previous works using NF [ 75 , 76 , 77 ], and sex seems not to be a modulator of NF learning performance [ 78 ], other authors have reported that girls with ADHD that remitted after NF treatment had shorter P300 latencies, an effect that was not observed in boys [ 79 ]. Thus, future research with larger and balanced samples should add the gender variable as a potential NF response moderator in adolescents with li-APF or ni-APF.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research (Krepel et al, 2020, presented as the principal study) replicated this effectiveness in a new sample of 114 patients treated with qEEG-informed neurofeedback, from a large multicentric dataset and investigated potential predictors of neurofeedback response.…”
Section: Visualizing Neurological Decision-making Pathways To Help CLmentioning
confidence: 99%